Maternal Experience Does Not Predict Fear Extinction and Anxiety-Like Behaviour in Primiparous Rats Post-weaning - Pestana, Jodie E.; McCutcheon, Tayla B.; Harmon-Jones, Sylvia K.; Richardson, Rick; Graham, Bronwyn M. (Frontiers in Global Women's Health, 2021)
Reproductive experience leads to long-lasting changes in anxiety-like behaviour and fear extinction, the laboratory model of exposure therapy for anxiety disorders. For example, fear extinction is influenced by estrous cycle in nulliparous (no reproductive experience) female rats, but this effect is abolished in primiparous (one reproductive experience) females. It is unclear whether such changes are driven by pregnancy, maternal experience of caring for offspring during the postpartum period, or a combination of both experiences. The present study sought to determine the influence of maternal experience (i.e., exposure to pups and mother-pup interactions) on fear extinction in primiparous rats. In Experiment 1, we tested whether pup exposure is necessary to mitigate estrous effects on fear extinction in primiparous rats. Age-matched nulliparous rats, primiparous rats, and primiparous rats who experienced pregnancy but not pup exposure, underwent fear conditioning on day 1 (two months post-parturition), extinction training during proestrus (high sex hormones) or metestrus (low sex hormones) on day 2, and extinction recall on day 3. Replicating past research, nulliparous rats showed impaired extinction recall when they were extinguished during metestrus compared to proestrus. In contrast, primiparous rats with and without pup exposure showed comparable extinction recall irrespective of estrous phase. In Experiment 2, we assessed whether naturally-occurring variation in mother-pup interactions predict future fear extinction performance and anxiety-like behaviour. During the first week of lactation, primiparous rats were measured for maternal behaviours towards pups. Primiparous rats were then tested on the light-dark box and elevated plus maze to measure anxiety-like behaviour and underwent a fear extinction protocol one month post-weaning. We found no significant correlations between maternal behaviour and fear extinction outcomes or anxiety-like behaviour. Our findings suggest that pregnancy, not maternal experience, mitigates the impact of estrous cycle on fear extinction. In addition, natural variation in maternal experience does not appear to contribute to variability in future fear extinction outcomes or anxiety-like behaviour in primiparous rats.